1989
DOI: 10.1177/014920638901500207
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Leadership: A Review of Theory and Research

Abstract: This article reviews and evaluates major theories of leadership and summarizes findings from empirical research on leadership. Major topics and controversies include leadership versus management, leader traits and skills, leader behavior and activities, leader power and influence, situational determinants of leader behavior, situational moderator variables, transformational leadership, importance of leadership for organizational effectiveness, and leadership as an attributional process. Methodological issues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
807
0
94

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,092 publications
(917 citation statements)
references
References 137 publications
16
807
0
94
Order By: Relevance
“…Job autonomy allows followers to become their own leader, as suggested by Manz and Sims (2001) and Yammarino (1994). Yukl (1989) stated that transformational leaders modify the beliefs and opinions of followers, causing greater follower autonomy, a finding confirmed by the present study that is also in line with the theory of Bass and Avolio (1990). Job autonomy produces a sense of job satisfaction that results in enhanced engagement.…”
Section: Test Of the Structural Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…Job autonomy allows followers to become their own leader, as suggested by Manz and Sims (2001) and Yammarino (1994). Yukl (1989) stated that transformational leaders modify the beliefs and opinions of followers, causing greater follower autonomy, a finding confirmed by the present study that is also in line with the theory of Bass and Avolio (1990). Job autonomy produces a sense of job satisfaction that results in enhanced engagement.…”
Section: Test Of the Structural Modelsupporting
confidence: 92%
“…If leadership is considered a means of affecting people's beliefs and behaviors (Yukl, 1989), transformational leaders can be said to be equipped to provide followers with a higher degree of autonomy (Bass & Avolio, 1990) so that they can become their own leaders (Yammarino, 1994). Indeed, experimental studies have demonstrated this causal relationship between transformational leadership and autonomy (Hackman & Oldham, 1976;Piccolo & Colquitt, 2006;Rich et al, 2010).…”
Section: Transformational Leadership Job Autonomy and Organizationalmentioning
confidence: 99%
“…434-457, Jul./Ago. 2016 www.anpad.org.br/rac (Kotter, 2001), e por isso tem recebido destaque tanto na literatura acadêmica (Yukl, 1989(Yukl, , 2012) quanto na mídia de negócios (e.g. : Schreyer, 2010).…”
Section: Referencial Teóricounclassified
“…It is beyond the scope of this paper to review the entire literature on leadership (see Hunt, 1999) however, we summarize some of the major approaches to studying leadership in order to make the following point (Bass et al, 1987;Fiedler, 1967;House, 1971;Steers et al, 1996;Yukl, 1989). Regardless of the partic-ular theoretical approach, leadership has been viewed largely as a way of directing and controlling foreseeable organizational futures.…”
Section: Leaders As Controllersmentioning
confidence: 99%